2007
DOI: 10.1002/cjce.5450850609
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of Acrylic Acid with 1,4‐Butanediol in a Batch Distillation Column Reactor over Amberlyst 15 Catalyst

Abstract: The esterification reaction of acrylic acid (AA) with 1,4‐butanediol (BD) to produce 4‐hydroxybutyl acrylate (HBA) was carried out in a batch reactive distillation mode over the Amberlyst 15 catalyst. The reactive distillation was highly desirable to increase the reaction rate of BD and eventually to obtain the high purity of HBA because the unreacted BD was not easily separable to the produced HBA after the reaction. The reaction pressure below 760 mm Hg was used to remove the by‐product water from the reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Some relevant and recent examples are esterification of acetic acid with methanol (Agreda & Partin, 1984;Chandrakar, Agarwal, Chand, & Wasewar, 2007), esterification of succinic acid and ethanol (Kolah, Asthana, Vu, Lira, & Miller, 2008a;Orjuela, Kolah, Lira, & Miller, 2011;Orjuela, Kolah, Hong, Lira, & Miller, 2012), reaction of citric acid (CA) with ethanol to give triethyl citrate (Kolah, Asthana, Vu, Lira, & Miller, 2008b) and CA (Kolah, Asthana, Vu, Lira, & Miller, 2007), esterification of 1-propanol and propionic acid (Kotora, Buchaly, Kreis, G orak, & Marko s, 2008;Altman et al, 2010;Cruz-Diaz et al, 2012;, esterification of acetic acid and ethanol (Yagyu et al, 2013) (which is the most studied reaction concerning reactive distillation for esterification (Drioli & Giorno, 2010)), esterification of acetic acid with n-butanol (Arpornwichanop, Koomsup, & Assabumrungrat, 2008), esterification of acryl acid with 1,4-butanediol to obtain 4-hydroxybutyl acrylate (Yang, Cho, Park, & Lee, 2007), reaction of lactic acid with n-butanol (Kumar & Mahajani, 2007), esterification of acrylic acid and n-butanol (Niesbach, Fuhrmeister, Keller, Lutze, & Gorak, 2012), synthesis of an n-butyl acetate system using a reactive distillation from an agroindustrial waste (i.e., starting from oil of Fusel) (Altomare, Labrador, Rodriguez, Morales, & Fernandez, 2012), and esterification of butyric acid and n-butanol (Ju et al, 2011). Some relevant and recent examples are esterification of acetic acid with methanol (Agreda & Partin, 1984;Chandrakar, Agarwal, Chand, & Wasewar, 2007), esterification of succinic acid and ethanol (Kolah, Asthana, Vu, Lira, & Miller, 2008a;Orjuela, Kolah, Lira, & Miller, 2011;Orjuela, Kolah, Hong, Lira, & Miller, 2012), reaction of citric acid (CA) with ethanol to give triethyl citrate (Kolah, Asthana, Vu, Lira, & Miller, 2008b) and CA (Kolah, Asthana, Vu, Lira, & Miller, 2007), esterification of 1-propanol and propionic acid …”
Section: Industrial Relevance Of Esterification Reactionsmentioning
confidence: 99%
“…Some relevant and recent examples are esterification of acetic acid with methanol (Agreda & Partin, 1984;Chandrakar, Agarwal, Chand, & Wasewar, 2007), esterification of succinic acid and ethanol (Kolah, Asthana, Vu, Lira, & Miller, 2008a;Orjuela, Kolah, Lira, & Miller, 2011;Orjuela, Kolah, Hong, Lira, & Miller, 2012), reaction of citric acid (CA) with ethanol to give triethyl citrate (Kolah, Asthana, Vu, Lira, & Miller, 2008b) and CA (Kolah, Asthana, Vu, Lira, & Miller, 2007), esterification of 1-propanol and propionic acid (Kotora, Buchaly, Kreis, G orak, & Marko s, 2008;Altman et al, 2010;Cruz-Diaz et al, 2012;, esterification of acetic acid and ethanol (Yagyu et al, 2013) (which is the most studied reaction concerning reactive distillation for esterification (Drioli & Giorno, 2010)), esterification of acetic acid with n-butanol (Arpornwichanop, Koomsup, & Assabumrungrat, 2008), esterification of acryl acid with 1,4-butanediol to obtain 4-hydroxybutyl acrylate (Yang, Cho, Park, & Lee, 2007), reaction of lactic acid with n-butanol (Kumar & Mahajani, 2007), esterification of acrylic acid and n-butanol (Niesbach, Fuhrmeister, Keller, Lutze, & Gorak, 2012), synthesis of an n-butyl acetate system using a reactive distillation from an agroindustrial waste (i.e., starting from oil of Fusel) (Altomare, Labrador, Rodriguez, Morales, & Fernandez, 2012), and esterification of butyric acid and n-butanol (Ju et al, 2011). Some relevant and recent examples are esterification of acetic acid with methanol (Agreda & Partin, 1984;Chandrakar, Agarwal, Chand, & Wasewar, 2007), esterification of succinic acid and ethanol (Kolah, Asthana, Vu, Lira, & Miller, 2008a;Orjuela, Kolah, Lira, & Miller, 2011;Orjuela, Kolah, Hong, Lira, & Miller, 2012), reaction of citric acid (CA) with ethanol to give triethyl citrate (Kolah, Asthana, Vu, Lira, & Miller, 2008b) and CA (Kolah, Asthana, Vu, Lira, & Miller, 2007), esterification of 1-propanol and propionic acid …”
Section: Industrial Relevance Of Esterification Reactionsmentioning
confidence: 99%
“…Therefore, alternative methods for direct monoesterification of acrylates with diols under mild conditions while controlling the byproduction of diol bis-acrylates are needed. Lee et al reported catalytic esterification of acrylic acid with 1,4-butanediol to produce 4-hydroxybutyl acrylate over several ion exchange resins . They precisely conducted kinetic studies of the condensation reaction over Amberlyst 15 in heterogeneous conditions via the quasi-homogeneous model to determine all kinetic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous esterification catalysts are reported in the literature for carrying out direct esterification of fatty alcohol with acrylic acid [1][2][3][4]. In general, all such reactions result in 90 % formation of fatty acrylate along with a range of by-products.…”
Section: Introductionmentioning
confidence: 99%
“…The major by-product is the Michael adduct, 3-(alkyloxy)-3-oxopropyl acrylate, formed by the addition of unreacted acrylic acid with the terminal double bond of alkyl acrylate. In an attempt to prepare fatty acrylate, we have carried out direct esterification of fatty alcohol with acrylic acid in the presence of a catalytic amount of NaHSO 4 . The reaction resulted in near equal formation of fatty acrylate and 3-(alkyloxy)-3-oxopropyl acrylate [5].…”
Section: Introductionmentioning
confidence: 99%